Updated perspective of EPAS1 and the role in pulmonary hypertension - Wang, Na; Hua, Jing; Fu, Yuhua; An, Jun; Chen, Xiangyu; Wang, Chuancui; Zheng, Yanghong; Wang, Feilong; Ji, Yingqun; Li, Qiang (Frontiers in Cell and Developmental Biology, 2023)
Pulmonary hypertension (PH) is a group of syndromes characterized by irreversible vascular remodeling and persistent elevation of pulmonary vascular resistance and pressure, leading to ultimately right heart failure and even death. Current therapeutic strategies mainly focus on symptoms alleviation by stimulating pulmonary vessel dilation. Unfortunately, the mechanism and interventional management of vascular remodeling are still yet unrevealed. Hypoxia plays a central role in the pathogenesis of PH and numerous studies have shown the relationship between PH and hypoxia-inducible factors family. EPAS1, known as hypoxia-inducible factor-2 alpha (HIF-2α), functions as a transcription factor participating in various cellular pathways. However, the detailed mechanism of EPAS1 has not been fully and systematically described. This article exhibited a comprehensive summary of EPAS1 including the molecular structure, biological function and regulatory network in PH and other relevant cardiovascular diseases, and furthermore, provided theoretical reference for the potential novel target for future PH intervention.